Deoxygenation of Phenolic Alkaloids by a Modified Pd/C-Catalyzed Hydrogenolysis Method - Lin, Chin-Ting; Lee, Shoie-Sheng (Synthesis, 2015)
A modified palladium on carbon (Pd/C) catalyzed hydrogenolysis method for the removal of the phenolic-OH group in phenolic alkaloids as the 1-phenyl-1H-tetrazol-5-yl derivative by the addition of magnesium metal or ammonium acetate in acetic acid is described. Five different types of isoquinoline alkaloids, i.e., phenanthrene alkaloid, aporphine, pavine, protoberberine, and 1-benzyltetrahydroisoquinoline, were used as reactants. The results indicate that the addition of either magnesium metal or ammonium acetate has the advantage of decreasing the amount of Pd/C and the accelerating reaction rate over the simple Pd/C-catalyzed hydrogenolysis, thus it is practical for larger-scale preparation of de-phenolated alkaloids for pharmacological study.
Keywords: phenolic alkaloids; de-phenolation; 1-phenyl-1H-tetrazol-5-yl ether; ammonium acetate; magnesium